UNLOADING OF FISH ACTIVITIES AT SENDANG BIRU, COASTAL FISHERIES PORT (PPP) PONDOKDADAP, MALANG REGENCY - Al Maky, Nuril Huda; Isdianto, Andik; Ariefandi, Muhammad Fikri; Kudrati, Amelinda Vivian; Tyas, Herlin Widi Aning; Yorarizka, Putri Devi; Pangestu, Wanda Suryani; Setyanto, Arief; Bintoro, Gatut; Putri, Berlania Mahardika; Fathah, Aulia Lanudia; Andrimida, Anthon; Luthfi, Oktiyas Muzaky (Directorate of Research and Community Service (DRPM), 2023)
The fishing port, which acts as a public agency, provides services and facilitates fishing activities for fishermen. One indicator that the service provided is already optimal is the minimum number of vessels in the process of dismantling fish in the port. The study aims to find out the fishing landing system and the number of ships that landed during the period September–August 2022. The method used is directly through field observations and collecting secondary data to supplement the data obtained. The system applied to each port is different. The port of Pondokdadap applies the queue method as well as the system of nahkoda, where the ship's documents must be submitted and the fisherman's number taken before landing. Boats that want to sell fish to the TPI must be equipped with a catch letter. In the period September–August 2022, the highest number of ships was found in June 2022, with 603. For the smallest number in January 2022, there were 22 ships. Based on the results obtained, it is known that the period of April–September has the highest number, while there is a decrease in the number in October–March. There was an increase in the number of vessels that carried out fishing, which was affected by the fishing season, with the high season in the Eastern season.